High prevalence of oncogenic MYD88 and CD79B mutations in diffuse large B-cell lymphomas presenting at immune-privileged sites - Kraan, W (Nature Publishing Group, 2013)
Activating mutations in CD79 and MYD88 have recently been found in a subset of diffuse large B-cell lymphoma (DLBCL), identifying B-cell receptor and MYD88 signalling as potential therapeutic targets for personalized treatment. Here, we report the prevalence of CD79B and MYD88 mutations and their relation to established clinical, phenotypic and molecular parameters in a large panel of DLBCLs. We show that these mutations often coexist and demonstrate that their presence is almost mutually exclusive with translocations of BCL2, BCL6 and cMYC, or Epstein–Bar virus infection. Intriguingly, MYD88 mutations were by far most prevalent in immune-privileged site-associated DLBCL (IP-DLBCL), presenting in central nervous system (75%) or testis (71%) and relatively uncommon in nodal (17%) and gastrointestinal tract lymphomas (11%). Our results suggest that MYD88 and CD79B mutations are important drivers of IP-DLBCLs and endow lymphoma-initiating cells with tissue-specific homing properties or a growth advantage in these barrier-protected tissues.